JAK inhibitors: a potential treatment for JDM in the context of the role of interferon-driven pathology - Meredyth G. Ll Wilkinson; Claire T. Deakin; Charalampia Papadopoulou; Despina Eleftheriou; Lucy R. Wedderburn (Pediatric Rheumatology Online Journal, 2021)
Abstract Juvenile Idiopathic Inflammatory Myopathies (IIM) are a group of rare diseases that are heterogeneous in terms of pathology that can include proximal muscle weakness, associated skin changes and systemic involvement. Despite options for treatment, many patients continue to suffer resistant disease and lasting side-effects. Advances in the understanding of the immunopathology and genetics underlying IIM may specify new therapeutic targets, particularly where conventional treatment has not achieved a clinical response. An upregulated type I interferon signature is strongly associated with disease and could be a prime target for developing more specific therapeutics. There are multiple components of the IFN pathway that could be targeted for blockade therapy. Downstream of the cytokine receptor complexes are the Janus kinase-signal transducers and activators of transcription (JAK-STAT) pathway, which consists of JAK1–3, TYK2, and STAT1–6. Therapeutic inhibitors have been developed to target components of this pathway. Promising results have been observed in case studies reporting the use of the JAK inhibitors, Baricitinib, Tofacitinib and Ruxolitinib in the treatment of refractory Juvenile Dermatomyositis (JDM). There is still the question of safety and efficacy for the use of JAK inhibitors in JDM that need to be addressed by clinical trials. Here we review the future for the use of JAK inhibitors as a treatment for JDM.